Antifungal Activity of Coumarin Against Candida albicans Is Related to Apoptosis - Jia, Chang; Zhang, Jian; Yu, Lili; Wang, Chenglu; Yang, Yijia; Rong, Xing; Xu, Ke; Chu, Maoping (Frontiers in Cellular and Infection Microbiology, 2019)
Coumarin (1,2-benzopyrone), an aromatic oxygen-containing heterocyclic compound, has various biological functions. Previous studies have demonstrated that coumarin and its derivatives exhibit antifungal activity against Candida albicans. In this study, we investigated the exact mechanism by which coumarin works against this fungus using Annexin V-FITC/PI double staining, TUNEL assay, and DAPI staining, and found that it induced a series of apoptotic features, including phosphatidylserine (PS) externalization, DNA fragmentation, and nuclear condensation. Moreover, it also induced cytochrome c release from the mitochondria to the cytoplasm and metacaspase activation. Further study revealed that intracellular reactive oxygen species (ROS) levels were increased and mitochondrial functions, such as mitochondrial membrane potential and mitochondrial morphology, were altered after treatment with coumarin. Cytosolic and mitochondrial Ca2+ levels were also found to be elevated. However, pretreatment with ruthenium red (RR), a known mitochondrial Ca2+ channel inhibitor, attenuated coumarin-mediated DNA fragmentation and metacaspase activity, indicating that the coumarin-induced C. albicans apoptosis is associated with mitochondrial Ca2+ influx. Finally, coumarin was found to be low-toxic and effective in prolonging the survival of C. albicans-infected mice. This study highlights the antifungal activity and mechanism of coumarin against C. albicans and provides a potential treatment strategy for C. albicans infection.